2006
DOI: 10.1111/j.1467-8535.2006.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Blending online learning with traditional approaches: changing practices

Abstract: Considerable claims have been made for the development of e-learning, either as stand-alone programmes or alongside more traditional approaches to teaching and learning, for students across school and tertiary education. National initiatives have improved the position of schools in terms of access to hardware and electronic networking, software and educational resources, and staff development. The potential of e-learning to improve learning and teaching, and in turn, attainment, may be contested by academics b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(83 citation statements)
references
References 9 publications
6
73
0
4
Order By: Relevance
“…www.ijacsa.thesai.org System quality indicates the quality of the ICT systems available in primary schools for teaching and learning activities. The quality of the ICT system significantly influences perceived usefulness [44], [47], [53], users' attitudes toward using the technology [44], [47], [49], [54], and users' behavioural intentions to use technologies [44], [49], [50], [55]. Unfortunately, in Saudi Arabia, teachers suffer from limited knowledge of the use and maintenance of ICT, as well as the basic technical and pedagogical skills for using technology in teaching, which negatively influences their current use of ICT [39], [40].…”
Section: Additional Constructs To Model Ict Use By the Teachersmentioning
confidence: 99%
“…www.ijacsa.thesai.org System quality indicates the quality of the ICT systems available in primary schools for teaching and learning activities. The quality of the ICT system significantly influences perceived usefulness [44], [47], [53], users' attitudes toward using the technology [44], [47], [49], [54], and users' behavioural intentions to use technologies [44], [49], [50], [55]. Unfortunately, in Saudi Arabia, teachers suffer from limited knowledge of the use and maintenance of ICT, as well as the basic technical and pedagogical skills for using technology in teaching, which negatively influences their current use of ICT [39], [40].…”
Section: Additional Constructs To Model Ict Use By the Teachersmentioning
confidence: 99%
“…Eventually it was found that a number of practising teachers are experiencing doubts in how to integrate effectively ICT tools into the existing curriculum. Condie and Livingston (2007) also found in a study that while some teachers continue to display a reluctance to engage with new technology, others remain fearful of trying new approaches which they perceive might have a negative impacts on examination results. The major barriers may be lack of confidence, lack of competence or lack of access to ICT resources.…”
Section: Introductionmentioning
confidence: 99%
“…Blended learning as an approach to learning has gained momentum because of its widespread integration in educational organizations and training centers [4] [5]. Utilization of blended learning (mixed learning) has proven to enhance and increase the effectiveness and efficiency of teaching and learning in both instructional and training environments [6] [7] asserted that modification of instructional practices takes place by mixing traditional learning with internet based learning which in turn leads students to: Focus on desired instructional skills such as critical thinking, carry out their responsibilities in the process of learning, and organize the process of learning resource utilization. Moreover, mixing traditional and electronic forms of learning (i.e., blended learning) provides learners with electronic instructional resources viewed to be lacking in traditional learning environments.…”
Section: Introductionmentioning
confidence: 99%